Quantitative Evaluation of the Transcriptional Activity of Steroid Hormone Receptor Mutants and Variants Using a Single Vector With Two Reporters and a Receptor Expression Cassette - Ji, Huimin; Li, Ying; Liu, Zhao; Tang, Min; Zou, Lihui; Su, Fei; Zhang, Yaqun; Zhang, Junhua; Li, Hexin; Li, Lin; Ai, Bin; Ma, Jie; et al. (Frontiers in Endocrinology, 2020)
Although the rapid development of high-throughput sequencing has led to the identification of a large number of truncated or mutated steroid hormone receptor (SHR) variants, their clinical relevance remains to be defined. A platform for functional analysis of these SHR variants in cells would be instrumental for better assessing their impact on normal physiology and SHR-associated diseases. Here we have developed a new reporter system that allows rapid and accurate assessment of the transcriptional activity of SHR variants in cells. The reporter is a single construct containing a firefly luciferase reporter gene, whose expression is under the control of a promoter with multiple steroid hormone responsive elements, and a Renilla luciferase reporter gene, that is constitutively expressed under the control of an internal ribosome entry site (IRES) and is not regulated by steroid hormones. The corresponding SHR (wildtype or mutant/variant) is also expressed from the same construct. Using this improved reporter system, we revealed a large spectrum of transactivation activities within a set of previously identified mutations and variations of the androgen receptor (AR), the estrogen receptor α (ERα) and the glucocorticoid receptor (GR) . This novel reporter system enables functional analysis of SHR mutants and variants in physiological and pathological settings, offering valuable preclinical or diagnostic information for the understanding and treatment of associated diseases.